Diseño de un programa de mantenimiento preventivo para INDSOL CIA. LTDA – Cotopaxi - Romero Pérez, Joffre David (2022)
The objective of this research project is the development of a preventive maintenance program for the paper industry INDSOL CIA. LTDA. To this end, the analysis of equipment by levels was carried out by assembling the manuals of each machine and its instructions and consequently be able to identify the components of each of them. A descriptive investigation was also carried out by applying bibliographic techniques and tools delivered information such as the FEAM matrix and criticality that facilitated to recognize the highest level of prevention that should be taken on the machinery, the same that represents in our study area, giving us a result that the cutting machine has a higher frequency factor than the other machines located in the industry. As well the information was also used to implement a tabulation of results where it is shown in a general way that the circular knitting machine has a high degree of causing any failure, also helped to include a coding of its equipment and its elements in such a way that it was possible to make a format for the preparation of technical data sheets. Several research methods were used in this project, including the qualitative method, which aided to detect the faults or breakdowns that the machinery may have and so be able to carry out the inspection routs and propose a master maintenance plan. Additionally, to obtaining all this information MaintanX was integrated in the industry to have digitized all the assets that are in INDOSOL. CIA. LTDA, in the same way the program is configured to notify the manager and the maintenance manager when, how and in which part of the machine maintenance should be executed.